2021
DOI: 10.1155/2021/9306760
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] MicroRNA‐133b Inhibition Restores EGFR Expression and Accelerates Diabetes‐Impaired Wound Healing

Abstract: Diabetic foot ulcers (DFUs) are caused by impairments in peripheral blood vessel angiogenesis and represent a great clinical challenge. Although various innovative techniques and drugs have been developed for treating DFUs, therapeutic outcomes remain unsatisfactory. Using the GEO database, we obtained transcriptomic microarray data for DFUs and control wounds and detected a significant downregulation of epidermal growth factor receptor (EGFR) in DFUs. We cultured human umbilical vein endothelial cells (HUVECs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…In addition, they found that hsa_circ_0084443 in HEKs can mediate the biological effects of PI3K, EGFR and ERK signaling pathways, but blocking these signaling pathways can inhibit the migration of HEKs (43). PI3K, EGFR and ERK signaling pathways are relatively mature and well-recognized effective pathways in the DFU healing process (69)(70)(71), which also laterally proves that circ_0084443 may play a key role in ulcer healing. SRTING database is a powerful online website for analyzing protein interactions (PPI network).…”
Section: Effect Of Circrnas On Human Epidermal Keratinocytesmentioning
confidence: 71%
“…In addition, they found that hsa_circ_0084443 in HEKs can mediate the biological effects of PI3K, EGFR and ERK signaling pathways, but blocking these signaling pathways can inhibit the migration of HEKs (43). PI3K, EGFR and ERK signaling pathways are relatively mature and well-recognized effective pathways in the DFU healing process (69)(70)(71), which also laterally proves that circ_0084443 may play a key role in ulcer healing. SRTING database is a powerful online website for analyzing protein interactions (PPI network).…”
Section: Effect Of Circrnas On Human Epidermal Keratinocytesmentioning
confidence: 71%
“…These ve hub genes have a good performance in the prediction and diagnosis of diabetic ulcers. A previous study found that EGRF knockdown decreased the proliferative capacity of cells and delayed the healing of fullthickness of back wounds in vivo 23 . Solute carrier family 2 member 1 (SLC2A1) has been related to diabetic microvascular complications in multiple projects 24 ; 25 .…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, miR-497 accelerated diabetic wound healing by decreasing the pro-inflammatory cytokines (IL-1β, IL-6, and TNF-α) and enhanced wound closure [ 329 ]. In another study, the inhibition of miR-133b resulted in accelerated wound healing in diabetes-impaired wound healing through the restoration of epidermal growth factor receptor (EGFR) expression and angiogenesis [ 330 ]. In a recent study, exosomal-cargoed miRs demonstrated a pivotal role in modulating angiogenesis in diabetic wound healing by regulating the expression of VEGF and downstream signaling transduction [ 303 ].…”
Section: Innovative Strategies For Wound Healingmentioning
confidence: 99%